Outcomes of lymphedema microsurgery for breast cancer-related lymphedema with or without microvascular breast reconstruction - Engel, Holger; Lin, Chia-Yu; Huang, Jung-Ju; Cheng, Ming-Huei (Annals of surgery, 2017)
Objective: This study investigated the outcome of lymphedema microsurgery with or without microsurgical breast reconstruction for breast cancer-related lymphedema (BCRL). Background: Complete decongestive therapy, lymphovenous anastomosis, and vascularized lymph node flap transfer are the 3 major treatment modalities for BCRL. Releasing axillary contracture and transferring a free flap may potentially improve the BCRL. Methods: Between 2004 and 2015, 124 patients with BCRL who underwent 3 treatment modalities without or with microsurgical breast reconstruction were included in this study as groups I and II, respectively. Patients were offered the lymphedema microsurgery depending on the availability of patent lymphatic ducts on indocyanine green lymphography if they failed to complete decongestive therapy. The circumferential difference, reduction rate, and episodes of cellulitis were used to evaluate the outcome of treatments. Results: Improvements in the circumferential difference (12.8 ± 4.2% vs 11.5 ± 5.3%), the reduction rate (20.4 ± 5.1% vs 14.7 ± 6%), and episodes of cellulitis (1.7 ± 1.1 vs 2.1 ± 2.4 times/yr) did not significantly differ between groups I and II (P = 0.06, 0.07, and 0.06, respectively). In both groups, vascularized lymph node flap transfer was significantly superior to lymphovenous anastomosis or complete decongestive therapy in terms of improvements in the circumferential difference, reduction rate and episodes of cellulitis (P = 0.04, 0.04, and 0.06, respectively). Conclusions: Microsurgical breast reconstruction did not improve the outcome of BCRL. Improvements in BCRL were better for lymphatic microsurgery than complete decongestive therapy. Moreover, vascularized lymph node flap transfer provided greater improvements in the BCRL than lymphovenous anastomosis.
Gesehen am 13.04.2018